Real-time Flood Monitoring Alert System with Lora and IoT - Yahya, Nurliyana Latifah; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2025)
This project focuses on developing a Real-Time Flood Monitoring and Alert System using LoRa and IoT technologies to enhance disaster preparedness in flood-prone areas, with the primary objective of continuously monitoring water levels, temperature, humidity, and water flow to provide timely alerts that mitigate flood risks. The methodology involves deploying an ultrasonic sensor, temperature and humidity sensors, and a water flow sensor connected to an ESP32 microcontroller, with data transmitted via LoRa to the ThingSpeak IoT platform for real-time monitoring. Testing at the UTHM pond yielded two key assessments: the monitored water levels, temperature, humidity, and water flow after rainfall, and the real-time data display on an OLED screen, confirming the system's functionality in providing immediate information to users. During moderate rainfall, the system successfully recorded a water level range of 25 cm to 26 cm, a temperature range of 27.73̊C to 27.57̊C, a humidity range of 87% to 92.31%, and a water flow range of 0 (an indication of no flow or movement detected). These results show how well the system detects environmental changes and how it may improve local authorities' ability to make decisions, eventually enhancing community safety in flood-prone areas. In conclusion, the project demonstrates a flood monitoring system, and it is suggested that the sensor network be expanded in the future and that mobile applications be used to increase user accessibility.